Simulation- and optimisation-oriented modelling considerations for the extraction of Ni(II) from its acidic aqueous chloride solutions into Alamine 336-m-xylene systems - SAYAR, NİHAT ALPAGU (ELSEVIER, 2009)
This study investigated the extractive recovery of Ni(II) from its aqueous acidic chloride solutions using a commercial extractant Alamine 336 diluted with m-xylene. A recently proposed generic model equation was originally implemented on the present system. Extraction equilibrium measurements were conducted as a function of initial metal concentration and acidic molarity of the aqueous phase and volume percentage of the active extractant in organic phase. The originally obtained data have been used to assess the simulating performance of the model equation. The measurements demonstrated that the model is able to simulate the operational output, the percentage of metal extracted, with a reasonable accuracy. The model has been used to predict the optimal values for key operational inputs and to develop a novel simulating window of operation for the solvent extraction of Ni(II) under present conditions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Extraction; Solvent; Nickel; Mathematical modelling; Optimisation; Simulation; DI(2-ETHYLHEXYL) PHOSPHORIC-ACID; SOLVENT-EXTRACTION; SULFATE-SOLUTIONS; CARBOXYLIC-ACIDS; SODIUM-SALTS; NICKEL; COBALT(II); SEPARATION; ZINC; EQUILIBRIUM